1993
DOI: 10.2307/3236075
|View full text |Cite
|
Sign up to set email alerts
|

Plant communities of the Stirling Range, Western Australia

Abstract: The Stirling Range is a mountain system of Proterozoic origin in the southern part of Western Australia, reaching an altitude of 1000 m; it consists of acid rocks and has a mediterranean climate with a rainfall of 500 ‐ 550 mm/yr. It is the only extensive mountain system of this portion of the continent and presents a rich endemic flora. The vegetation of the area was investigated from 1984 to 1992; 68 phytosoci‐ological releves, ecological observations and extensive floris‐tic collections were made. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The campo rupestre is dominated by forbs and graminoids, interspersed with evergreen sclerophyllous shrubs, while other OCBILs are better described as heathlands. The low proportion of annual species (Le Stradic et al 2015a) is also found in fynbos (Goldblatt and Manning 2002) and kwongkan (Pignatti et al 1993;Mucina et al 2014). Rosettes are common in species belonging to Eriocaulaceae, Velloziaceae, Asteraceae, Apiaceae, Bromeliaceae and others (Fig.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The campo rupestre is dominated by forbs and graminoids, interspersed with evergreen sclerophyllous shrubs, while other OCBILs are better described as heathlands. The low proportion of annual species (Le Stradic et al 2015a) is also found in fynbos (Goldblatt and Manning 2002) and kwongkan (Pignatti et al 1993;Mucina et al 2014). Rosettes are common in species belonging to Eriocaulaceae, Velloziaceae, Asteraceae, Apiaceae, Bromeliaceae and others (Fig.…”
Section: Introductionmentioning
confidence: 91%
“…5b). Giant rosettes of Vellozia (Velloziaceae) and Lobelia (Campanulaceae) in campo rupestre are similar to those of Senecio (Asteraceae) in afroalpine vegetation (Hedberg 1973), Espeletia (Asteraceae) in páramos (Ramsay and Oxley 1997), and Xanthorrhoea (Xanthorrhoeaceae) and Kingia (Dasypogonaceae) in kwongkan (Pignatti et al 1993;Mucina et al 2014). Basal rosettes of Bromeliaceae and Eriocaulaceae are conspicuous in campo rupestre, as they are in tepuis (Huber 2006), páramos (Ramsay and Oxley 1997), fynbos (Manning 2007) and kwongkan .…”
Section: Introductionmentioning
confidence: 94%
“…– Xanthorrhoea platyphylla Bedford’ as listed by Pignatti et al . (). It will be interesting to find whether all Australian species of Cysteochila are restricted to Proteaceae, particularly Grevillea and Hakea species (neither Drake & Ruhoff nor Cassis & Gross list any hosts for Australian species of Cysteochila ).…”
Section: Discussionmentioning
confidence: 97%
“…The unique nature of the ecosystem known as the Eastern Stirling Range Montane Heath and Thicket Community was first described by Ludwig Diels in 1906 (Gibson ), and subsequently in more detail by Pignatti et al . () and most recently by Barrett (, ). Long‐term monitoring and historical records show that the Montane Heath and Thicket has undergone substantial decline in recent decades (Keith et al .…”
Section: Introductionmentioning
confidence: 93%